2010
DOI: 10.1037/a0017777
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific association between psychopathic traits and electrodermal reactivity in children.

Abstract: This study investigated the relationship of skin conductance response (SCR) to a child psychopathy measure. Blunted electrodermal activity is a theoretically important characteristic of psychopathy, but has not been fully explored in preadolescents or females. We tested the hypothesis that reduced SCR magnitude is associated with psychopathic-like traits in boys and girls. Participants were drawn from an ethnically diverse community sample of 9-10 year old twins. Given the fact that members of each twin pair w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
1
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 67 publications
4
56
1
5
Order By: Relevance
“…Although genetic and environmental influences on psychopathic traits may be comparable in boys and girls (Ficks, Dong, & Waldman, 2014), other putative causal risk factors may be divergent (Krischer & Sevecke, 2008; see Verona & Vitale, 2006 for review). Reduced skin conductance responses were positively associated with the interpersonal facet of psychopathic traits (including narcissism) in boys but not girls during a countdown task (Isen et al, 2010). Similarly, men homozygous for the 5-HTTLPR short allele, but not women, were more likely to administer higher shocks (i.e., aggression) to a confederate under stress (Verona, Joiner, Johnson, & Bender, 2006).…”
mentioning
confidence: 99%
“…Although genetic and environmental influences on psychopathic traits may be comparable in boys and girls (Ficks, Dong, & Waldman, 2014), other putative causal risk factors may be divergent (Krischer & Sevecke, 2008; see Verona & Vitale, 2006 for review). Reduced skin conductance responses were positively associated with the interpersonal facet of psychopathic traits (including narcissism) in boys but not girls during a countdown task (Isen et al, 2010). Similarly, men homozygous for the 5-HTTLPR short allele, but not women, were more likely to administer higher shocks (i.e., aggression) to a confederate under stress (Verona, Joiner, Johnson, & Bender, 2006).…”
mentioning
confidence: 99%
“…If no response was detected, then the magnitude for that particular trial assumed a value of zero rather than being omitted. We decided against confining our analyses to nonzero values (i.e., amplitudes) in order to exploit the full set of observations (Isen, Raine, Baker, Dawson, Bezdjian, & Lozano, 2010; Tuvblad, Gao, Isen, Botwick, Raine, & Baker, 2012). …”
Section: Methodsmentioning
confidence: 99%
“…Two studies were found that youths with both CD and higher CU traits showed a lower changing of heart rate to emotionally reminiscent ilms compared to youths with CD but without CU traits [132,133]. In addition, it was demonstrated that when anticipating aversive stimuli, skin conductance reactivity reduced in adolescents with psychopathic traits compared to controls [134,135]. Additionally, CU traits were negatively related to skin conductance reactivity when responding to peer provocation in a sample of detained adolescent boys [136].…”
Section: Other Biological Factorsmentioning
confidence: 98%